Improvement of Learning Process and Outcomes Using an Open-Ended Approach in Mathematics Education in Elementary Schools - Utama, Refli Surya; Wahyu Hidayat, Puput; Agrita, Tri Wera (Master of Civic Innovation and Education Technology, 2025)
This classroom action research was conducted in grade IV of SDN 04//II Jaya Setia with the background of low mathematics learning outcomes of students. The average daily test score was only 50, still below the school's Target Learning Completion Criteria (KKTP) of 70. This condition prompted the research to be conducted with the aim of improving the learning process and outcomes through the application of the Open Ended approach. The research was conducted in two cycles, each covering the stages of planning, implementation, observation, and reflection. The research subjects consisted of 22 students, while the data collection techniques used observation and learning outcome tests. The research results showed that the application of the Open Ended approach was very effective and significantly improved students' learning outcomes. In Cycle I, learning achievement reached only 59.09%, then increased to 86.36% in Cycle II. This improvement indicates that the Open-Ended approach encourages students' activity, creativity, and understanding, particularly in the material on multiplication and division of decimal numbers. Since the success indicators were achieved, the research was terminated in Cycle II. The implications of this study are that the Open-Ended approach can serve as an alternative strategy for mathematics instruction in elementary schools. Teachers can utilize it not only for decimal number topics but also for other materials that require idea exploration and problem-solving.